RELATIONSHIP OF DISCIPLINARY AND DISMISSAL PROCEEDINGS IN LABOUR LAW OF THE REPUBLIC OF SERBIA - Midžović, Milica (Glasnik Advokatske komore Vojvodine, 2023)
The subject of research in this work was a current regulation of the institute of disciplinary and dismissal proceedings in the labour law of the Republic of Serbia. In fact, in the general regime of employment relations, the institute of disciplinary liability and disciplinary procedure is regulated within the institute of termination of employment, in the segment that deals with breaches of work obligations as cause of dismissal. Since these are two the most important and sensitive institutes in the sphere of labour relations, whose injury can ultimately lead to the termination of employment and be the endangerment of employee existence, it is necessary for this institutes to be adequately regulated. Therefore, during the research process were used a deepened interview, internet survey, analysis of legal provisions, comparative legal analysis and analysis of court judgments. All of this methods, in some parts confirms the hypothesis that shortened, summary, disciplinary proceedings, as it currently exists, indirectly burden the judiciary and lead to an increase in the number of dismissals given to employees. Respondents in 93% believe that employer can abuse their disciplinary power. As many as 19.4% of respondents responded that they were in a position of unlawfully termination of employment and 19.3% that they were fired without compliance with the rules of dismissal. A high percentage of respondents, 67% believe that legal provisions should help establish a fairer relationship between the employee and the employer. The interviewed experts agree with the claim that the court should indeed be a last means to protect an employee and in order to protect the rights of the employee and respect the policies “in favour laborem”, it is necessary to change, supplement and amend the legal provisions. Also, the impact of decisions of the Constitutional Court of the Republic of Serbia on the legal order and protection of human rights under the auspices of the European Court of Human Rights is very important, especially in cases of violation of the right to a fair trial and hearing within a reasonable time. The author comes to the conclusion that disciplinary proceedings are highly vulnerable to abuse unless there are clear norms governing them, so it would be useful to return the institute of internal protection in the general labour law regime. Also, the deadlines for starting the proceedings could be reduced by half from the six months and a year. It would also be very useful if there was the specialized labour law courts such as in England, France, Germany. Also based on the survey, it came to the conclusion that unions can indeed have a greater role and importance in protecting employee rights. And a proposal for a mandatory attempt to resolve disputes peacefully before addressing the court could give positive results.